Digital payment transformation: a strategic differentiator in indonesia’s microfinance innovation - Revi Lonna; Siti Azizah U.A; I Made Sukresna (LifeSciFi, 2025)
This study aims to analyze the transformation of digital payments from manual to mobile systems as a strategic differentiator in Indonesia’s microfinance innovation. Using a qualitative method, data were collected through in-depth interviews with microfinance industry players, regulators, and users of digital financial services. The results indicate that the adoption of mobile-based digital payments not only improves operational efficiency but also expands access to financial services for communities previously underserved by formal financial systems. This transformation fosters the creation of a more inclusive and adaptive microfinance ecosystem in response to technological advancements. Furthermore, payment digitalization provides a competitive advantage for microfinance institutions in facing market competition and meeting the increasingly dynamic needs of customers. The study recommends strengthening collaboration between industry players, government, and technology providers to accelerate the adoption of digital payments in the microfinance sector. These findings are expected to serve as a strategic reference for the sustainable development of microfinance innovation in Indonesia.